Preference for flexibility and random choice: An experimental analysis - Mark Dean; John McNeill (Brown University, Department of Economics, 2014)
People may be uncertain about future preferences, leading to both a preference for flexibility in choice between menus and stochastic choice from menus. This paper describes an experimental test of preference uncertainty in a realeffort task. We observe subjects' preferences over menus of work contracts, along with their choices of effort levels from those contracts. Our results suggest that preference uncertainty is important: 48% of our subjects exhibited strict preference for flexibility. A model of preference uncertainty (Ahn and Sarver (2013)) well describes the relationship between choice of and from menus: subjects willing to pay to include an option in a contact were more likely to use that option, and those that used an option were prepared to pay for it. We show that the introduction of an explicit stochastic element to the contract increased preference for flexibility, suggesting a causal role for uncertainty in menu preferences.
Keywords: 330